Business ethics and the role of context: institutionalism, history and comparisons in the Asia Pacific region. Issue 3 (2nd July 2016) - Rowley, Chris; Oh, Ingyu
Abstract: The role of business ethics is important and key to organizations and management. To what extent business ethics are actually new or fashionable or universally applicable is an interesting question. Business ethics can usefully use the explanatory power of New Institutionalism and Modes of Exchange as Asia has been a rich ground of contests between competing economic and ethical views of how economic norms and institutions are organized. Explaining the evolutionary similarities and differences of institutionalizing business ethics in this region was the context of history and comparisons to better ground business ethics literature, both empirically and theoretically.